Pendekatan Humanistik dalam Membangun Motivasi Belajar Siswa pada Pembelajaran Geografi di Madrasah Aliyah DDI Paria - Mutmainnah Mutmainnah (Geosfera: Jurnal Penelitian Geografi, 2026)
The humanistic approach is important in geography learning because it places students at the center of the learning process by considering their potential, emotions, and learning needs. However, geography learning in schools still tends to be conventional, resulting in low student engagement and learning motivation. This study aims to analyze the implementation of the humanistic approach and its influence on students’ learning motivation in geography learning at Madrasah Aliyah DDI Paria. This study employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The results indicate that the humanistic approach was implemented through student-centered learning, open dialogue, appreciation of students’ opinions, and the use of interactive and contextual learning methods. This implementation increased students’ learning motivation, active participation, self-confidence, and interest in geography learning. In addition, the humanistic approach created a more empathetic, communicative, and comfortable learning environment for students. In conclusion, the humanistic approach is effective in improving students’ learning motivation and supporting the creation of empathetic and interactive geography learning.